Design-led solution for curbing crime: the case study of a major entertainment precinct in Perth, Western Australia. Issue 1 (2nd January 2023) - Jonescu, Emil E.; Olatunji, Oluwole A.; Foo, Jason
ABSTRACT: This research is built around extant theories on crime prevention through environmental design. An extensive observational appraisal of Northbridge, Perth's premier entertainment precinct was undertaken, using an adaptation of Jan Gehl's Quality Criteria research methodology. This involves an assessment matrix for evaluating urban space for protection, comfort and enjoyment. Moreover, the research employed an iterative design-led process, embedding affordance and surveillance principles into an urban design proposition for the case study precinct. Features of the proposed solution include design elements that were identified to dissuade impact, frequency and severity of criminal activities.